Understanding and supporting block play: Video observation research on preschoolers' block play to identify features associated with the development of abstract thinking. Issue 5 (3rd June 2017) - Otsuka, Kaoru; Jay, Tim
ABSTRACT: This article reports on a study conducted to investigate the development of abstract thinking in preschool children (ages from three years to four years old) in a nursery school in England. Adopting a social influence approach, the researcher engaged in 'close listening' to document children's ideas expressed in various representations through video observation. The aim was to identify behaviours connected with features of the functional dependency relationship – a cognitive function that connects symbolic representations with abstract thinking. The article presents three episodes to demonstrate three dominating features, which are (i) child/child sharing of thinking and adult and child sharing of thinking ; (ii) pause for reflection ; and (iii) satisfaction as a result of self-directed play. These features were identified as signs of learning, and were highlighted as phenomena that can help practitioners to understand the value of quality play and so provide adequate time and space for young children and plan for a meaningful learning environment. The study has also revealed the importance of block play in promoting abstract thinking.